The CORRELATION BETWEEN DEPTH OF ENDOTRACHEAL TUBE PLACEMENT AND PAIN IN VENTILATED PATIENTS IN THE ICU OF PKU MUHAMMADIYAH GAMPING HOSPITAL - Alfiana Sukma Ayu; Aisyah Nur Azizah; Ellyda Septiani Pramita (Journal of Indonesian Anesthesiology Nursing, 2026)
Background: Endotracheal tube (ETT) insertion is an invasive procedure commonly performed in patients receiving mechanical ventilation in the Intensive Care Unit (ICU). Improper ETT placement depth may lead to various complications, including unplanned extubation, airway irritation, mucosal injury, and increased pain. Pain in critically ill patients is often difficult to assess due to communication limitations caused by mechanical ventilation and sedation. Therefore, an objective assessment instrument is required, one of which is the Critical Care Pain Observation Tool (CPOT). Methods: This study employed a quantitative design with a cross-sectional approach. The study sample consisted of 55 mechanically ventilated patients selected using an accidental sampling technique. Data were collected using the Critical Care Pain Observation Tool (CPOT) assessment form and analyzed using the Spearman Rank test. Results: The findings showed that most patients had an optimal endotracheal tube placement depth, while the majority experienced moderate pain levels. Statistical analysis revealed a significant relationship between the depth of endotracheal tube placement and pain (p = 0.001), with a moderate correlation strength (r = 0.450). Conclusion: There is a significant correlation between the depth of endotracheal tube placement and pain in mechanically ventilated patients in the ICU of PKU Muhammadiyah Gamping Hospital.